Improved diagnostic performance of CASPAR criteria with integration of ultrasound - Geng, Yan; Song, Zhibo; Zhang, Xiaohui; Deng, Xuerong; Wang, Yu; Zhang, Zhuoli (Frontiers in Immunology, 2022)
Background: The difficulty in determining synovitis, tenosynovitis or enthesitis by physical examination (PE) has limited the diagnostic capability of CASPAR for psoriatic arthritis (PsA). Therefore, we aimed to evaluate the diagnostic utility of CASPAR with integration of ultrasound (US). Methods: The patients with hint of PsA were enrolled. Besides routine PE for tender or swollen joint, enthesitis, dactylitis, US was performed to evaluate peripheral joints, entheses and tendons. The additional value of US to CASPAR criteria was analyzed. Results: 326 consecutive patients with164 PsA and 162 non-PsA were enrolled. 162 non-PsA patients consisted of 58 psoriasis (PsO), 27 osteoarthritis with PsO/family history of PsO, 5 fibromyalgia with PsO, 69 sero-negative rheumatoid arthritis, and 3 undifferentiated arthritis. Significantly higher frequencies of tenosynovitis and enthesitis on US and new bone formation on X-ray were found in PsA than non-PsA patients (59.1% vs. 13.0%; 63.4% vs. 14.2%; 62.2% vs. 8.0%, p<0.01 for all). Logistic regression analysis showed that dactylitis (OR=12.0, p<0.01), family history of PsO/PsA (OR=3.1, p<0.05), nail involvement (OR=3.5, p=0.01), new bone formation on X-ray (OR=14.8, p<0.01) and tenosynovitis on US (OR=21.3, p<0.01), enthesitis on US (OR=21.7, p<0.01) were independent risk factors for PsA. By combined US tenosynovitis and/or enthesitis, the diagnostic utility of CASPAR criteria was improved, with superior specificity (91.4% vs. 84.0%) and similar sensitivity (95.7% vs. 94.5%). Replacing X-ray by US or adding US, the CASPAR criteria showed comparable sensitivity and specificity for PsA diagnosis. The diagnostic accuracy was 89.3% for CASPAR criteria based on PE, 93.6% for CASPAR added with US, and 93.3% for CASPAR with US replacing X-ray. Conclusion: The diagnostic utility of the CASPAR was improved by integrating tenosynovitis and/or enthesitis on US. US provides additional value for PsA recognition.